Fishermen Community Participation in Tiku Awareness Tourism Group on Sustainable Tourism Development. - Zamzami, Lucky; Iwabuchi, Akifumi (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2024)
Implementing sustainable tourism development within tourist villages has emerged as a growing trend in the tourism industry, catering to the contemporary needs of tourists and serving as a valuable economic resource. It is also regarded as a gauge of the successful execution of sustainable tourism within local communities, exemplifying their active involvement in harnessing the tourism potential of their regions. This article seeks to chronicle the execution of sustainable tourism development in coastal areas, focusing on village-based tourism due to its profound impact on local economies and the transformations in people's ways of life. To illustrate this, a case study was conducted in South Tiku Village, Tanjung Mutiara District, Agam Regency. The research employed a descriptive qualitative modeling approach and in-depth interviews involving village stakeholders, the Awareness Tourism Group (Kelompok Sadar Wisata), and the South Tiku Tourism Village community. As a result, it became evident that the residents of Tiku Tourist Village have effectively harnessed their village's potential through sustainable tourism development. This is substantiated by the notable increase in income among the South Tiku Tourist Village community, primarily attributable to tourism-related activities. Furthermore, this transformation has seen former fishermen transition into tourism entrepreneurs, reshaping their livelihoods.